N‐terminal fragment of the type‐B natriuretic peptide (NT‐proBNP) contributes to a simple new frailty score in patients with newly diagnosed multiple myeloma. Issue 11 (29th August 2016) - Milani, Paolo; Vincent Rajkumar, S.; Merlini, Giampaolo; Kumar, Shaji; Gertz, Morie A.; Palladini, Giovanni; Lacy, Martha Q.; Buadi, Francis K.; Hayman, Suzanne R.; Leung, Nelson; Dingli, David; Lust, John A.; et al.
Abstract : Multiple myeloma (MM) patient frailty has been delineated primarily by age and ECOG performance score (PS) and recently by the IMWG frailty score based on functional status [Activity of Daily Living (ADL) and Instrumental‐ADL scores], comorbidities [Charlson‐comorbidity‐index (CCI)] and age. It was hypothesized that N‐terminal natriuretic peptide type B (NT‐proBNP) might be both a more convenient measure of frailty and a predictor of overall survival (OS). Three‐hundred and fifty‐one consecutive symptomatic MM patients who were seen at Mayo Clinic within 30 days of diagnosis and who had blood stored were eligible. Data from the first visit was abstracted and used to calculate an ADL, CCI, and measure the NT‐proBNP level. The best cutoff of NT‐proBNP predicting OS was 300 ng/L. Variables predictive for OS were ECOG‐PS, age, CCI, ADL, ISS, revised‐ISS, and NT‐proBNP. On multivariate analysis age ≥70, PS ≥2, and NT‐proBNP ≥300 were independent predictors of survival. Patients were assigned a score of 1 for each of these variables, creating stages I–IV with scores of 0–3 points, respectively. The median OS from diagnosis was not reached, 58, 28, and 18 months ( P  < 0.0001), respectively. This frailty risk schema was independent of initial therapy and the revised‐ISS. NT‐proBNP is a useful predictor of survival independent of age and PS. It is a widely available biomarker that could be added to the panel of laboratory tests of newly diagnosed MM patients and serve as a simple and objective tool of determining frailty in clinical practice. Am. J. Hematol. 91:1129–1134, 2016. © 2016 Wiley Periodicals, Inc.